RELEVANSI SEMBOYAN KI HAJAR DEWANTARA SEBAGAI PEDOMAN GURU - Nafiah; Siti Aisyah; Indah Shanum Muliati (Berugak Baca, 2025)
This research aims to determine the relevance of Ki Hajar Dewantara's motto as a teacher's guide. The method applied in this research is qualitative by conducting literary research using journals and books available on the internet. The research results show that the three mottos coined by Ki Hajar Dewantara are Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani. Having a strong bond, with the teacher as a facilitator must be a role model for students, because in the world of formal education, it is the teacher who controls the students' cognitive, emotional and psychomotor development. There is a very strong influence on the education system in Indonesia which no longer applies like the education system outside but has implemented a character and culture education system in the world of education. Due to the existence of an education system, an ideal educator can become a role model for his students so that they can determine the true future of the world.